2017
DOI: 10.1111/liv.13467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating hepatocellular carcinoma cell lines for tumour samples using within‐sample relative expression orderings of genes

Abstract: Caution should be taken for using hepatocellular carcinoma cell lines. Our results should be helpful to select proper hepatocellular carcinoma cell lines for biological experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Furthermore, we selected four HCC cells with different genetic backgrounds to detect the level of GNPDA1 in HCC cells. HepG2 was derived from the liver tissue of a fifteen-year-old Caucasian American male with hepatoblastoma, and does not synthesize hepatitis B virus surface antigen (HBsAg); 29 Hep-3B was derived from the liver tissue of a 8-year-old black male with hepatocellular carcinoma, and synthesizes HBsAg; 30 Huh-7 was derived from the liver tissue of a Japanese man with highly differentiated hepatocellular carcinoma, and does not synthesize HBsAg; HepG2, Hep-3B and Huh7 are highly representative of HCC and show the same metastatic properties of the high-risk metastatic HCC tissues; 31 SMMC-7721 cell line was established in China. We found that compared with L-02, the GNPDA1 levels in SMMC-7721, HepG2 and Huh7 were higher, while there was no significant difference in the level of GNPDA1 between Hep-3B and L-02, which may be affected by HBsAg.…”
mentioning
confidence: 99%
“…Furthermore, we selected four HCC cells with different genetic backgrounds to detect the level of GNPDA1 in HCC cells. HepG2 was derived from the liver tissue of a fifteen-year-old Caucasian American male with hepatoblastoma, and does not synthesize hepatitis B virus surface antigen (HBsAg); 29 Hep-3B was derived from the liver tissue of a 8-year-old black male with hepatocellular carcinoma, and synthesizes HBsAg; 30 Huh-7 was derived from the liver tissue of a Japanese man with highly differentiated hepatocellular carcinoma, and does not synthesize HBsAg; HepG2, Hep-3B and Huh7 are highly representative of HCC and show the same metastatic properties of the high-risk metastatic HCC tissues; 31 SMMC-7721 cell line was established in China. We found that compared with L-02, the GNPDA1 levels in SMMC-7721, HepG2 and Huh7 were higher, while there was no significant difference in the level of GNPDA1 between Hep-3B and L-02, which may be affected by HBsAg.…”
mentioning
confidence: 99%
“…The frequent interactions of naturally abundant albumin with cells in the body as well as its wide exogenous applications in the biomedical and pharmaceutical industries (Dennis et al, 2002;Sleep, Cameron & Evans, 2013) prompted us to study the effects of albumin on cells. We have selected HepG2/C3A carcinoma cells because they originate from hepatocytes (Aden et al, 1979) and have been used as a model for studying hepatocellular carcinoma (Chen et al, 2015;Ao et al, 2017) as well as normal hepatocyte functions (Nibourg et al, 2012;Gaskell et al, 2016). Hepatocytes play an important role in the clearance of albumin bound substances (Meijer & Van der Sluijs, 1989), therefore some of these albumin interacting properties can potentially be used in targeting hepatocellular carcinoma or studying the effects of pathologically modified albumin on cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent interactions of naturally abundant albumin with cells in the body as well as its wide exogenous applications in the biomedical and pharmaceutical industries (Dennis et al, 2002;Sleep, Cameron & Evans, 2013) prompted us to study the effects of albumin on cells. We have selected HepG2/C3A carcinoma cells because they originate from hepatocytes (Aden et al, 1979) and have been used as a model for studying hepatocellular carcinoma (Chen et al, 2015;Ao et al, 2017) as well as normal hepatocyte functions (Nibourg et al, 2012;Gaskell et al, 2016). Hepatocytes play an important role in the clearance of albumin bound substances (Meijer & van der Sluijs, 1989), therefore some of these albumin interacting properties can potentially be used in targeting hepatocellular carcinoma or studying the effects of pathologically modified albumin on cellular function.…”
Section: Discussionmentioning
confidence: 99%